2018
DOI: 10.1007/5584_2018_229
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and Influenza-Like Viruses: Frequent Infections in Children Under 14 Years of Age During the 2016/2017 Epidemic Season

Abstract: Influenza is an infectious disease that is a common cause of infection among children. The main reason for it is the extremely low percentage of vaccinated people in Poland. In the 2016/2017 epidemic season more than 3,000 tests from children up to age 14 were examined. The dominance of subtype A/H3N2/ (40.9%) was confirmed. The evaluation was stratified by three age groups (0-4, 5-9, and 10-14 years), which revealed significant differences. The highest number of samples was available in the 0-4 years group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Among the influenza A viruses, infections with subtype A/H1N1/pdm09 dominated over A/H3N2/. This season had entirely different characteristics from the preceding 2016/17 season in Poland when no A/H1N1/pdm09 infections had been reported among children (Cieślak et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Among the influenza A viruses, infections with subtype A/H1N1/pdm09 dominated over A/H3N2/. This season had entirely different characteristics from the preceding 2016/17 season in Poland when no A/H1N1/pdm09 infections had been reported among children (Cieślak et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The finding was different from the previously observed result as a general property of French influenza epidemics only to seasons exhibiting recurrent patterns, which can be applied to the incidence time series of different countries and different diseases. The children with age of >14 were examined in the 2016/2017 epidemic season, and the results demonstrated that children due to immature immunity are at particular risk for influenza (Cieslak et al, 2018). In the United States, Baltrusaitis et al found that data from novel influenza surveillance systems can complement with traditional healthcare-based systems at multiple spatial resolutions (Baltrusaitis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The limited data on RSV infections suggest that among non-influenza viruses detected in positive samples (constituting approx. 50% of all positive samples), RSV is the predominant one, accounting for over 96% of cases among children aged 0 to 14 years [ 28 , 29 ] and 55% to 91% of cases among the general population ( Table 1 [ 30 , 31 , 32 , 33 , 34 , 35 ]). Therefore, RSV is the major agent responsible for non-influenza viral respiratory infections in Poland [ 31 , 36 ].…”
Section: Resultsmentioning
confidence: 99%